Toponimi Kuno Di Daerah Aliran Sungai Nagara, Kalimantan Selatan - Hindarto, Imam; Ida Bagus Putu Prajna Yogi (Badan Riset dan Inovasi Nasional (BRIN), 2024)
The Nagara river basin is an area for developing cultural history in South Kalimantan. The Hikayat Banjar and Tutur Candi tell a lot about historical events and places in this area. Archaeological evidence in this area also confirms the existence of cultural activities in the past. Through archaeo-toponymic studies, this article aims to understand the cultural history of this region. The problem in this article will discuss the meaning of place names and their relationship to the existence of archaeological sites. This research was carried out using a literature study. The data sources used in this study consist of the Hikayat Banjar, Tutur Candi, Archaeological Research Reports, and landform maps. The analysis used is the first archaeo-toponomic model. This analysis requires clarity of place names, locations, and their role in history. The analysis resulted in the interpretation that three place names played an important role in the course of cultural history in this area, namely Ujung Tanah, Candi, and Nagara. The third toponymy is spread along the Nagara River Basin and each of its meanings is related to events in the two literary works. Archaeological sites discovered in these places indicate cultural activities in the past.